Effects of epidural analgesia exposure during parturition on autism spectrum disorder in newborns: A systematic review and meta-analysis based on cohort study - Wang, Xiaobo; Li, Jie; Liu, Dezhao (Frontiers in Psychiatry, 2022)
Background Labor epidural analgesia (LEA) is one of the most effective and widely used approaches for pain relief during parturition. we conducted this meta-analysis to evaluate the association between LEA exposure during parturition and ASD in newborns. Methods PubMed, Cochrane Library, EMBASE and Web of Science database were searched from inception to January 2, 2022 to identify related articles. Literature screening was carried out strictly according to the inclusion and exclusion criteria, and data were extracted and imported into STATA 15.0 software for meta-analysis. Results A total of 5 studies with 1763454 participants were included. A statistically significant correlation was observed between LEA and changed ASD (RR = 1.20, 95%CI (1.17, 1.24)), and the correlation between LEA and ASD were analyzed by univariate HR (ES = 1.34, 95%CI(1.27,1.40), P < 0.05) and Multivariate HR (ES = 1.13, 95%CI (1.05,1.21), P < 0.05). Limitation First, few studies were included, and most patients were from the United States. Second, the included studies were observational cohort designs, which cannot avoid selection and measurement bias. Third, the results of the included studies were heterogeneous, and a more detailed subgroup analysis was not possible. Conclusion There is a correlation between LEA during parturition and the risk of ASD in newborns. The Newborn whose mother received LEA during her birth-giving might be more likely to develop ASD.